A Critical Review on the Reconstruction of the Manouchehri House in Kashan - Mitra Azad; Rafee Darsouei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Revitalization plays an important role in protecting the historical buildings, which simultaneously protects the culture and the body. This approach has played an important economic role. Today, many revitalization projects, regardless of the importance of cultural factors and with a purely economic perspective, have caused numerous damages in historical contexts. Therefore, by regulating the principles of revitalization, new use can be assigned to the monument. Reviewing the strengths and weaknesses of these plans can be effective. This underscores the importance of the critique of revitalization projects and how to intervene in them. In addition to cultural and economic returns, principled restoration is also an effective approach to encourage people to participate and invest in the restoration of historic collections. Historic houses are the most remnants of Iran's architectural heritage, the multiplicity and diversity of that in historical contexts provide good potential as urban catalysts. This research has been done by reviewing documents, field studies, and libraries and by the qualitative research method. The purpose of this research is to analyze the effective features in reviving one of the historical houses of Kashan city called "Manouchehri House" which is considered as a case study in this regard due to being a candidate for the Aga-Khan-Award and cultural economic prosperity provided by a tourist-accommodation.